Paisaje, ambiente y forma urbana en la cuenca del río Reconquista - Williams, Dr. Arq. Fernando (Universidad Nacional del Litoral, 2017)
Landscape, environment and urban form in the Reconquista river basin The approach of the “Urban Rivers” project The present article draws on the preliminary results of “Urban Rivers”, a research  project carried out at the Institute of Architecture, UNSAM, aimed at studying the problems of urban watersheds, in particular, the one along the Reconquista River, the second largest river basin within the Buenos Aires conurbation, with a population of almost 3 million. As in other urban basins, the lower zones concentrate the most critical social and environmental problems due to the existence of large scale landfills and high density informal settlements. Departing from a realization of the complexity of those problems and from an understanding of these territories as essentially heterotopic, the present article gathers the contributions of two of the four lines of research within the project, and use landscape, environment and urban form as diferent perspectives to approach the study of this particular territory. The article concludes with a reflection on the necessary redefinition of the role played by research projects within the Institute of Architecture, where researchers have established new links with undergraduate and postgraduate courses.